TOWARD GLOBALIZATION: AN INDONESIAN EXPERIENCE IN ENGLISH LANGUAGE TEACHING - Ied Veda Sitepu (Prodi Sastra Inggris UKI, 2025)
English language is acknowledged as a foreign language in Indonesia. Since the nation’s independence, it has been taught in secondary and tertiary education levels and later on, even in primary level, due to increasing demand of the skills in international communication. It was believed that the sooner the language is introduced, the better. Globalization that reduced country borders and gave way to interconnectedness has given more opportunities to the people in the global world, provided that they have English language skill proficiency. How has Indonesia prepared its students in the mastery of the language and how is the teaching of the language in Indonesia? Indonesian secondary and tertiary education institutions need competent teachers to help the students learn the language. This paper will therefore discuss, with the status of English language in Indonesia, how does Indonesia prepare the students for the globalization, in terms of language teaching and because Indonesia is a large country, with a massive number of secondary and tertiary education institutions, how collaboration and innovation in language teaching play important roles in strengthening English language teaching in Indonesia, especially as the country seeks to prepare students for global competitiveness.